2021
DOI: 10.1002/tox.23326
|View full text |Cite
|
Sign up to set email alerts
|

The protective role of resveratrol against sulfoxaflor‐induced toxicity in testis of adult male rats

Abstract: This work was designed to explore the protective role of resveratrol (RES) against sulfoxaflor (Sulfx)‐induced reproductive toxicity in adult male rats. The animals were divided into six groups: Control group, Sulfx treated groups (79.5 and 205 mg/kg/day), RES treated group (20 mg/kg/day), RES + Sulfx treated groups (20 mg/kg Res + 79.5 or 205 mg/kg Sulfx) orally for 28 consecutive days. Testicular samples were collected from all groups at the end of the treatment period. Tissue supernatants were isolated for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 66 publications
3
3
0
Order By: Relevance
“…These findings indicated increased LPO and oxidative stress as a result of TMX treatment. This was in agreement with [77], who discovered that daily oral ingestion of Sulfx for 28 days at low (79.5 mg/kg) and high (205 mg/kg) doses resulted in significant increase in testicular MDA, GSSG, and NOx level versus a dosedependent drop in GSH content. [51] discovered that giving imidacloprid (22.5 mg/kg b.wt) by orogastric each day for 56 days caused testicular free radical damage, as evidenced by exceptionally high malondialdehyde (MDA) levels, a noticeable downturn in antioxidant enzyme activity, and lower glutathione (GSH) and total antioxidant capacity (TAC) levels.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings indicated increased LPO and oxidative stress as a result of TMX treatment. This was in agreement with [77], who discovered that daily oral ingestion of Sulfx for 28 days at low (79.5 mg/kg) and high (205 mg/kg) doses resulted in significant increase in testicular MDA, GSSG, and NOx level versus a dosedependent drop in GSH content. [51] discovered that giving imidacloprid (22.5 mg/kg b.wt) by orogastric each day for 56 days caused testicular free radical damage, as evidenced by exceptionally high malondialdehyde (MDA) levels, a noticeable downturn in antioxidant enzyme activity, and lower glutathione (GSH) and total antioxidant capacity (TAC) levels.…”
Section: Discussionsupporting
confidence: 91%
“…11 (2022) In comparison to the control group, the current findings revealed considerable DNA damage in the treatment groups in male testis as measured by percent DNA in tail, Comet percent, tail length, tail moment, and olive moment. This was in line with the findings of [77], who discovered that Sulfx treatment caused a significant increase in testicular DNA fragmentation, indicating poor spermatogenesis [53]. On the other hand, found that TMX administration did not result in considerable sperm DNA fragmentation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…RSV has been shown to ameliorate toxicant-induced male reproductive toxicity by attenuating oxidative stress and apoptosis. 23,57 And, there is now growing evidence that PTE protects the body's organs from environmental toxins by counteracting oxidative stress. Better yet, PTE has better oral utilization relative to RSV.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, an increment in abnormal sperm morphology and DNA damage observed after 4 weeks after SXF administration revealed that SFX has more adverse effects on male reproductive tissue. Furthermore, another way SFX affects the function of the male reproductive system is to damage DNA (Said et al 2021 ), since the morphology of sperm is organized by various autosomal and Y-specific genes (Bansal et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%